Value of Chromosome 9p21 Polymorphism for Prediction of Cardiovascular Mortality in Han Chinese Without Coronary Lesions. Issue 39 (September 2015) - Lee, I-Te; Liang, Kae-Woei; Wang, Jun-Sing; Lee, Wen-Jane; Chen, Yii-der Ida; Lin, Shih-Yi; Lee, Wen-Lieng; Sheu, Wayne H.-H.; Lymperopoulos., Anastasios
<x xml:space="preserve">Abstract</x> Abstract Variants at chromosome 9p21 are associated with coronary artery disease (CAD). However, the longitudinal effects of 9p21 variants on cardiovascular mortality remain controversial and may depend on whether the patient has CAD. We tested the hypothesis that the single-nucleotide polymorphism (SNP) rs4977574 is associated longitudinally with cardiovascular death in patients without detectable coronary lesions. We enrolled patients who underwent coronary angiography for angina pectoris but had normal angiographic findings. Laboratory analyses and rs4977574 TaqMan genotyping were performed using fasting blood samples collected during hospitalization. Cardiovascular and all-cause mortality rates were acquired from a national database. Among the 679 enrolled subjects with neither myocardial infarction nor an angiographic coronary lesion, 28 (19.0%) of the 147 homozygous GG carriers suffered a cardiovascular death, compared with 63 (11.8%) of the 532 subjects with the AG or AA genotype during the median 12.3 years (interquartile range 8.6–12.7 years) of follow-up. In a recessive model, cardiovascular mortality was significantly higher in subjects with the GG genotype than in those with the other genotypes (hazard ratio, 1.69, 95% confidence interval 1.08 to 2.64; P = 0.021). In this follow-up study, rs4977574, a tag SNP at chromosome 9p21, was shown to be associated with cardiovascular mortality in Taiwanese patients with angina pectoris but no coronary lesions.